2020
DOI: 10.1590/1806-9282.66.9.1247
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the incidence and prevalence of laryngeal papillomatosis in São Paulo State (Brasil)

Abstract: SUMMARY BACKGROUND: Recurrent laryngeal papillomatosis, caused by the Human Papilloma Virus, has a significant economic impact worldwide and there are no epidemiological data of this disease in Brasil. OBJECTIVE: The objective of the study was to estimate the incidence and prevalence of laryngeal papillomatosis of some otorhinolaryngology centers in São Paulo State (Brasil). METHODS: A questionnaire containing data on the number of new and follow-up cases diagnosed with laryngeal papillomatosis was sent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…The cohort studies reported in the literature had relatively small sample sizes of RRP patients. Ximenes Filho et al 20 conducted a ten-year retrospective cohort study with 44 patients, while Matos et al 23 have also evaluated 25 patients with RRP, and in a third study, Silva et al 36 performed a ten-year retrospective study with 21 patients. These three studies were carried out in Sao Paulo State.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort studies reported in the literature had relatively small sample sizes of RRP patients. Ximenes Filho et al 20 conducted a ten-year retrospective cohort study with 44 patients, while Matos et al 23 have also evaluated 25 patients with RRP, and in a third study, Silva et al 36 performed a ten-year retrospective study with 21 patients. These three studies were carried out in Sao Paulo State.…”
Section: Discussionmentioning
confidence: 99%
“…Causada pelo HPV, principalmente subtipos 6 e 11 e caracteriza-se pela presença de lesões proliferativas exofíticas e recidivantes sobre a mucosa das vias aérea, em especial na laringe. 1,2 O diagnóstico é feito geralmente entre 2 a 5 anos de idade, um ano após início dos sintomas que em 75% das crianças iniciam antes dos 5 anos de idade. 3 De maneira geral, inicia-se na comissura e terço anterior das pregas vocais, podendo afetar, posteriormente, todas as porções da laringe, envolvendo, em alguns casos, também traqueia, brônquios e parênquima pulmonar.…”
Section: Perguntaunclassified
“…À medida que os PL aumentam de tamanho, eles começam a obstruir as vias aéreas, manifestando-se com falta de ar progressiva e estridor inspiratório agudo. 1,3 A transmissão da doença não está totalmente compreendida; no entanto, a transmissão sexual e vaginal durante a gravidez é discutida, uma vez que crianças podem adquirir a doença no canal de parto, após contato com condiloma acuminado. 1 Resposta: B.…”
Section: Perguntaunclassified
“…Humano o VPH, ésta es la lesión benigna más frecuente causada por este virus, sobre todo por los tipos 6 y 11 hasta en 50 a 100% de casos, también pueden deberse a otros subtipos como el 16 y 18 de mayor riesgo oncológico (2,5).…”
Section: Es Causada Por Un Virus Adn De La Familia Papillomaviridae L...unclassified
“…La Papilomatosis Respiratoria Recurrente (PRR) se define como el crecimiento benigno recurrente de lesiones papilomatosas en el tracto aerodigestivo superior que puede comprometer la vocalización, la respiración y la deglución.1 No es una enfermedad muy frecuente pero aun así implica un gran impacto económico y en la calidad de vida de los pacientes, las estimaciones de la prevalencia e incidencia de la PRR son imprecisas, en nuestra región en el estudio del 2020 en los cinco mayores centros regionales de Salud del interior de São Paulo Brasil se encontró una incidencia y prevalencia de 1,87-11,46 y 6,86-22,92 por 1.000.000 de habitantes respectivamente (1,2).…”
Section: Introductionunclassified